The AMA handbook of business writing : the ultimate guide to style, grammar, usage, punctuation, construction, and formatting - Wilson, K. 1958- (American Management Association, 2010)
This handbook is a complete A to Z reference on everything you need to produce top-quality documents. You'll find more than 600 pages of instantly accessible, thoroughly useful information for getting any job done.
Keywords: Commercial correspondence -- Handbooks, manuals, etc.; Business writing -- Handbooks, manuals, etc.; English language -- Business English -- Handbooks, manuals, etc.; elektronické knihy; electronic books